Avelumab: a promising PD-L1 inhibitor for lung cancer (with inconvenient infusional reactions) - Tanvetyanon, Tawee (Translational Cancer Research, 2017)
PD-1 and PD-L1 inhibitors have become an important treatment option for advanced non-small cell lung cancer (NSCLC) (1). In the first-line setting, a PD-1 inhibitor pembrolizumab by itself or in combination with chemotherapy has received a regulatory approval for marketing in the United States (2). In a previously treated setting, another PD-1 inhibitor nivolumab (3) and a PD-L1 inhibitor atezolizumab (4) have also been approved for clinical use. In addition, other agents which are already available in the United States for various indications include durvalumab (5) and avelumab (6). Durvalumab and avelumab are a PD-L1 inhibitor, currently approved for urothelial carcinoma; avelumab is also approved for Merkel cell carcinoma. Both drugs are being studied for clinical indications related to NSCLC. Although to date, there has been no head-to-head comparison between PD-1 and PD-L1 agents, it appears that PD-1 agent may be slightly more efficacious—as well as toxic—than PD-L1 agent based on the frequency of tumor responses and serious adverse events observed in NSCLC clinical trials. Nevertheless, it remains unclear how much this subtle difference will impact on overall survival and quality of life in the real world setting. At this time, these drugs are often considered as belonging to the same therapeutic class with potential cross resistance as well as cross efficacy. Within this increasingly crowded therapeutic arena, newer agents may be facing an identity crisis.